Advanced routing techniques for wireless ad hoc networks - Tan, Chee Wah (2009)
The pervasiveness of wireless communications and the need to connect “anyplace, anytime, anywhere” has led to the development of wireless ad hoc networks. While the current IEEE 802.11 standard allows wireless communications to be established in a LAN (local area network) like manner, its support for ad hoc communications is limited. This is because the IEEE 802.11 standard requires an established infrastructure to be in place for routing and other networking tasks. Wireless devices which move out of radio communication range of this network infrastructure cannot retain their network connectivity. In contrast, in a wireless ad hoc network, these devices may still be able to communicate with each other as long as each device is within the communication range of other devices, even if there is no established network infrastructure in place. This is achieved by having all the wireless devices perform additional functions of data forwarding and routing to support wireless communications, apart from being the eventual source and destination of the data.